Persepsi Masyarakat Atas Penggunaan Transportasi Online (Studi Kasus Di Kota Bima) - Muniarty, Puji; Rimawan, M; Ovriyadin, Ovriyadin; Haryanti, Intisari; Sulami, Neti (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2025)
Basically, there will definitely be pros and cons to the use of online transportation between Grab users. It is not surprising that currently the use of online transportation, commonly called grab, is in great demand by peoPle in Bima City, NTB, considering that currently Covid-19 is really troubling the psychology of the community. Covid-19 changes people's buying behavior because information is increasingly clear that the impact of Covid-19 shows a high mortality rate. So that people are limited by space and fear of interacting directly with sellers or consumers. The study population was users of online transportation with the use of sampling techniques, namely purposive sampling, quantitative approach, followed by in-depth interviews through interviews with 7 informants. The data analysis technique used the mix method, namely to measure the accuracy of the data statistically by using one sample test, while qualitatively by describing the results of the interview. The results of the study explain that the use of online transportation (GRAB) has a significant positive effect. Public perception is proven that it can influence people's views of online transportation. Because Grab provides services to the community, from performance to attributes it can affect public perceptions. The public perception of online transportation is good or bad, depending on the performance of the Grab drive it self.